Seismic Behavior of Three-Story Prestressed Fabricated Concrete Frame under Dynamic and Low Reversed Cyclic Loading. (10th September 2018) - Song, Manrong; He, Jiaxuan; Liu, Yuan; Zhang, Hang; Ge, Chenjun; Jin, Yadong; Liu, Bingkang; Huang, Shenjiang; Liu, Yan
Abstract : Precast concrete structure is the building industrialization of the sure route. It can realize the construction process of low energy consumption and low emission and effectively meet the green development requirements of the construction industry. Based on prestressing technique, the connections of the precast concrete structure obtain prestress producing integrate joints and continuous frames, which improve the seismic safety and are applied widely in the earthquake area. To study seismic behavior of prestressed fabricated concrete frame structure, the experiments on the concrete frame under dynamic loading and low reversed cyclic loading were carried out. The single-span three-story prestressed fabricated concrete frame can accurately represent the load-carrying capability and the failure mechanism of multistory frame. Results of the study show that experimental specimens have good behaviors such as full hysteresis curves, proper displacement restoring capacity, and energy dissipation; the maximum interlayer drift ratio arrives 0.27% which has no damage to the frame in small earthquakes subjected to the 102 gal peak ground acceleration; the frame is repairable in moderate earthquakes when the maximal interlayer drift ratio arrives 0.73% subjected to the 204 gal peak ground acceleration; plastic hinges appeared at the ends of beam under low reversed cyclic loading firstly where the section curvature ductility factor ranges from 3.64 to 5.62; biaxial compression is acquired at beam-column joints with the help of column axial force and horizontal prestressing force; the beam fails before the column in the prestressed fabricated concrete frame at interlayer drift ratio between 1.56% and 2.56%.